2008
DOI: 10.1007/s11105-008-0067-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis of Drought Stress-Responsive Proteins in Hippophae rhamnoides L.

Abstract: Hippophae rhamnoides L. is uniquely capable of growing well under extreme environmental conditions such as water deficit, low temperature, and high altitude. Such tolerance invokes much interest in understanding the biology of this plant species and its utilization potential. In this study, analysis of drought stress-responsive proteins in H. rhamnoides was conducted wherein greenhousegrown seedlings were subjected to drought stress. By using proteomic techniques, proteins, extracted from leaves, were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…However, in this study, interestingly the RuBisCO levels in leaves of drought-resistant strain FS43 and sensitive strain FS38 were both up-regulated following the water deprivation (Tab.1). This result is in contrast with other publications, which reported decreased levels (Vu and Gesch, 1999) or even abolition of RuBisCO, following drought stress (Reddy et al, 2004), but in agreement with contrary reports from Rizhsky (2002) and Xu (2009).Therefore, the role of RuBisCO in water deficit response needs further investigations. Functional enzymes of anti-permeation play an important role in the fir drought stress response In plants, osmoregulation is an important physiological mechanism to adapt to adversities and an effective way to tolerate water deficiency.…”
supporting
confidence: 60%
“…However, in this study, interestingly the RuBisCO levels in leaves of drought-resistant strain FS43 and sensitive strain FS38 were both up-regulated following the water deprivation (Tab.1). This result is in contrast with other publications, which reported decreased levels (Vu and Gesch, 1999) or even abolition of RuBisCO, following drought stress (Reddy et al, 2004), but in agreement with contrary reports from Rizhsky (2002) and Xu (2009).Therefore, the role of RuBisCO in water deficit response needs further investigations. Functional enzymes of anti-permeation play an important role in the fir drought stress response In plants, osmoregulation is an important physiological mechanism to adapt to adversities and an effective way to tolerate water deficiency.…”
supporting
confidence: 60%
“…Moreover, its extensive root system aids to soil conservation (Trajkovski and Jeppsson 1999). Cascades of genes imparting adaptive nature to seabuckthorn to withstand various abiotic stresses and genes related to biosynthesis of various bioactive compounds, have generated substantial interest among researchers all over the world (Yang et al 2005;Guo et al 2007;Xu et al 2009;Ghangal et al 2012;Fatima et al 2012;Ghangal et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al (2008) reported drought stress responsive proteome in the seedling and leaf of sea buckthorn. A total of 55 proteins showed change in abundance in drought.…”
Section: Introductionmentioning
confidence: 99%